Passivity-Based Pose Synchronization in Three Dimensions - Hatanaka, T.; Igarashi, Y.; Fujita, M.; Spong, M. W. (IEEE transactions on automatic control, 2012)
This paper addresses passivity-based pose synchronization in the Special Euclidean group SE (3) . We first develop a passivity-based distributed velocity input law to achieve pose synchronization. We next show that the pose synchronizes exponentially fast under an assumption on the initial states of the bodies, with an exponential convergence rate given by algebraic connectivity of interconnection graphs. We also prove pose synchronization in the presence of communication delays and topology switches. We moreover give further extensions of the present law, where desirable velocities and collision avoidance are taken into account. Finally, the effectiveness of the present inputs is demonstrated through numerical simulations and experiments on a planar (2D) test bed.